Faktor yang Mempengaruhi Perilaku Pencegahan Infeksi Saluran Kemih pada Mahasiswi Keperawatan di Universitas Airlangga - Nursalam Nursalam; Regyana Mutiara Guti; Tiyas Kusumaningrum (FORIKES, 2021)
Urinary tract infections is a health problem often less awareness by the community especially students. Student’s bad habits can induce the incidence of urinary tract infections. The purpose of this study was to determine the factors associated with the prevention behavior of urinary tract infections at Fakultas Keperawatan Universitas Airlangga. The design for this study was descriptive analytic with cross-sectional approach. This study was conducted at Fakultas Keperawatan Universitas Airlangga. Total sample was 160 respondents, taken in accordance with the inclusion criteria and sampling using a simple random sampling technique. The independent variables in this study were knowledge, attitudes, accessibility of health facilities, and social support. The dependent variable in this study was the behavior of prevention urinary tract infections in nursing students. The data were collected using questionnaire. Data were analyzed by using Logistic Regression. The results showed that there were relationships between knowledge (p=0.011), attitude (p=0.000), and social support (p=0.007) with the behavior of urinary tract infection prevention in college students. The most dominant factors that correlate the behavior of urinary tract infection prevention are attitude (Exp (B) = 4.392), social support (Exp (B) = 2.449) and knowledge (Exp (B) = 0.357). Knowledge, attitudes and social support were fundamental factors in building personal behaviour. Prevention of urinary tract infection behavior can be done optimally if students have good knowledge, positive attitude and social support. Keywords: behavior; prevention; urinary tract infection ABSTRAK Infeksi saluran kemih merupakan masalah kesehatan sering diremehkan oleh masyarakat khususnya mahasiswa. Kebiasaan yang kurang baik dapat menjadi faktor terjadinya infeksi saluran kemih. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan perilaku pencegahan infeksi saluran kemih pada mahasiswi keperawatan Universitas Airlangga. Rancangan penelitian ini adalah deskriptif analitik dengan pendekatan cross-sectional. Penelitian ini dilakukan di Fakultas Keperawatan Universitas Airlangga. Total sampel adalah 160 responden, diambil sesuai dengan kriteria inklusi dan pengambilan sampel menggunakan teknik simple random sampling. Variabel independen pada penelitian ini adalah pengetahuan, sikap, keterjangkauan sarana kesehatan, dan dukungan sosial. Variabel dependen pada penelitian ini adalah perilaku pencegahan infeksi saluran kemih pada mahasiswi keperawatan. Instrumen yang digunakan adalah kuesioner. Analisis menggunakan uji statistik Regresi Logistik dengan derajat signifikasi p